The Impact Of Applying Digital Transformation On The Effectiveness Of Accounting Information an Analytical Study Of The Opinions Of a Sample Of Employees In Private Banks In Baghdad Governorate - Ali Ibrahim Ahmed; Mohammed Ahmed Mhmood (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The current research aims to measure the impact of applying digital transformation represented by (technologies, digitization of operations, databases, human cadres) on the effectiveness of accounting information represented by (appropriateness of accounting information, and reliability of accounting information), among a sample of employees in private banks in Baghdad Governorate, with a strength of (183) employees. In order to achieve the research objective, the questionnaire was adopted to collect data related to the research variables, and the descriptive analytical approach was adopted in the research and then analyzed by adopting some statistical methods such as (arithmetic mean, standard deviation, linear correlation coefficient, simple and multiple regression coefficient), and the results were reached using statistical programs such as (SPSS.V.29) and (Amos.V.26) to analyze the data to reach the conclusions, the most prominent of which was that digital transformation contributes to completing routine operations, reducing the time required to complete tasks, increasing accuracy in operations, and reducing human errors through the use of digital systems.